The description of a cryptic species related to the pan-Amazonian frog Allobates femoralis (Boulenger 1883) (Anura: Aromobatidae) - Simões, Pedro Ivo; Lima, Albertina P.; Farias, Izeni Pires (Zootaxa, 2010)
We describe a new species of litter frog from western Brazilian Amazon previously referred to as Allobates femoralis (Boulenger 1883). The new species is allopatric to A. femoralis and its known occurrence is restricted to terra-firme forests on the left bank of the upper Madeira River and southeastern State of Acre. This species is distinguished from A. femoralis and from other species in the A. femoralis group by presenting two-note advertisement calls and conspicuous reddish-orange color on ventral surfaces of hind limbs and posterior abdomen. Phylogenetic analyses based on a fragment of the 16S rRNA mitochondrial gene suggest the new species is the sister group to a clade referred to as A. femoralis occurring in southern State of Acre, from which it is distinguished by six unambiguous nucleotide substitutions, in addition to exclusive advertisement calls and color patterns. The new species is more distantly related to A. femoralis sensu stricto occurring near the A. femoralis type locality in the Peruvian Amazon. Summarizing evidence from molecular phylogenetic analysis, genetic distances and available data on advertisement calls, we identify one possible case of genetic introgression between lineages in this group and highlight the potential for the description of more species within the A. femoralis complex.